Oral reading fluency and comprehension in Kenya: reading acquisition in a multilingual environment. (21st April 2015) - Piper, Benjamin; Schroeder, Leila; Trudell, Barbara
Abstract : Reading research has shown that variable relationships exist between measures of oral reading fluency and reading comprehension, depending on whether the language of the text is the reader's first language or an additional language. This paper explores this phenomenon, using reading assessment data for 2, 000 Kenyan children in two or three languages: English, Kiswahili and one of two mother tongues, Dholuo or Gikuyu. The assessment data allowed us to compare reading and comprehension rates across languages. The data indicated that many children could read English words more easily than words in Kiswahili or their mother tongue; nevertheless, their reading comprehension was significantly lower in English than in Kiswahili, Dholuo or Gikuyu. The paper concludes that emphasising English reading fluency is an inefficient route to gaining reading comprehension skills because pupils are actually attaining minimal oral reading fluency in English and only modest comprehension skills in their own languages. The evidence also demonstrates that Kenya's national language policy of mother tongue as a medium of instruction in the early primary grades is consistently ignored in practice.